Times of Scarcity : Selected Notes from the Third European Urban Summer School - (:unkn) unknown (AESOP; European Urban Summer School (EUSS), University of Westminster, 2012)
The volume represents a collection of reflections and student works rather than a peer-reviewed proceedings. Texts are presented in their original form, including the authors’ style, language, and references. This volume contains selected notes, essays, and reflections from participants and tutors of the Third European Urban Summer School (EUSS), held in London in 2012. The theme of the school was Scarcity and Creativity in the Built Environment, focusing on the exploration and design of new approaches to urban planning and design under conditions of resource scarcity, uncertainty, and continuous change. Contributions include theoretical and methodological reflections, case studies from the London neighbourhood of Bromley-by-Bow, as well as manifestos and experimental texts by young researchers and practitioners. The publication reflects the interdisciplinary and international character of EUSS, bringing together participants from diverse academic and professional backgrounds.
Keywords: European Urban Summer School; urban planning; scarcity; creativity; Bromley-by-Bow; London; urban change; participation; EUSS 2012; AESOP